Spontaneous rupture of an unscarred uterus during pregnancy: an interesting case report - K., Durga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine rupture in pregnancy is very rare and potentially catastrophic for both mother and foetus. The most common cause of uterine rupture is giving away of previous caesarean uterine scar. Spontaneous rupture of an unscarred uterus during pregnancy is a rare occurrence. We hereby present a rare case of a spontaneous complete uterine rupture in a non-labouring unscarred uterus of a 33-year-old nulliparous woman at 35 weeks of gestation. She presented with lower abdomen pain and decreased foetal movements at Institute of Obstetrics and Gynaecology, Chennai. Even before getting into labour, patient suddenly collapsed, and emergency laparotomy was proceeded in view of suspicious concealed abruption. There was frank hemoperitoneum along with a dead baby in the abdominal cavity. There was rupture of uterine fundus extending from one cornual end to the other and closure of uterine rent proceeded. Spontaneous rupture of uterus occurs when there is an upper segment uterine scar. She had a past history of eventful uterine curettage which was the risk factor for uterine rupture.